The Potential Effects of Dielectric Barrier Discharge Plasma on the Extraction Efficiency of Bioactive Compounds in Radix Paeoniae Alba - Jin, Tao; Zhou, Zhenghua; Zhou, Jian; Ouyang, Wenchong; Wu, Zhengwei (Frontiers in Nutrition, 2021)
Radix paeoniae alba (RPA) is a kind of herbal medicine of traditional Chinese medicine (TCM), and widely used for the treatment of liver diseases and rheumatoid arthritis in clinical practices. As a result of low extraction efficiency of RPA by conventional method, many patients bear high dosage. In this study, four exposure doses of dielectric barrier discharge (DBD) plasma (0, 60, 120 and 180s) were applied to modify the extraction efficiency of paeoniflorin, benzoylpaeoniflorin, tannic acid, gallic acid, 2'-hydroxy-4'-methoxyacetophenone and polysaccharide in RPA. Finally, the application of plasma for 180s exhibited 24.6% and 12.0% (p<0.001) increasement of tannic acid and polysaccharide contents, however, 2.1% (p<0.05) and 5.4% (p<0.001) reductions of paeoniflorin and gallic acid composition respectively, and no significant difference (p>0.05) results obtained from benzoylpaeoniflorin and 2'-Hydroxy-4'-methoxyacetophenone contents. Our results of Scanning electron microscopy (SEM), Automatic specific surface area and pore analyzer, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and Thermal gravimetric analysis (TGA) indicated that DBD plasma can etch the surface and graft polymerization by reactive species so that change the water/oil holding capacity and eventually change the extraction efficiency of bioactive compounds in RPA. Overall, our observations provide a scientific foundation for modifying the extraction efficiency of bioactive ingredients related to the pharmacological activities of RPA.